Pengendalian Penyakit Budok dengan Fungisida dan Deteksi Residu pada Daun Nilam - Christanti Sumardiyono; Sedyo Hartono; Nasrun Nasrun; Sukamto Sukamto (Jurnal Fitopatologi Indonesia, 2013)
Budok caused by Synchytrium pogostemonis is the important and destructive disease on patchouli plant (Pogostemon cablin). Chemical control must be done in incidence with high disease intensity and prediction of outbreak. The experiment was done using benomyl (Benlate 50 WP) and cuprous oxide (Kocide 77WP) 0.1%, 0.2% and mixture of both ( 1 g cuprous oxide and 1 g L-1 benomyl). Patchouli plant was sprayed eight times with one week interval. Harvesting was done two weeks after the end of spraying. Residue analysis of Cu was done with AAS and benomyl residue with HPLC. The result showed that 0.1% benomyl significantly reduced the disease intensity. The other treatments showed lower result. Harvested patchouli plants treated with 0.1% benomyl showed higher yield compare with 0.2% benomyl and cuprous oxyde. Cu residue in dried leaves was between 460 ppm and 950 ppm. Residue of benomyl was 54–100 ppb. Diseased seedling still can be used after spraying by benomyl four times with 2 weeks interval.